2001
DOI: 10.1007/s004320100255
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of the AP-1 family in endometrial cancer: correlations with cell cycle regulators

Abstract: Our results indicate that the AP-1 family of transcription factors is probably implicated in the regulation of cell cycle progression and control in endometrial carcinomas. In particular, c-fos might be an additional negative prognostic factor and/or implicated in tumor progression in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…Several of these proteins (IRS2, Tensin-3͞TEM6, BCAR3, and ␤-catenin) are involved in cytoplasmic signaling. This group, as well as the transcriptional activator Jun-C͞D, are known to either be up-regulated or more active in some cancer cells (22)(23)(24)(25)(26)(27)(28)(29). Thus, the phosphopeptides displayed on cancer cells and not JY BLCL are preferentially derived from source proteins associated with cytoplasmic signaling pathways and cellular transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these proteins (IRS2, Tensin-3͞TEM6, BCAR3, and ␤-catenin) are involved in cytoplasmic signaling. This group, as well as the transcriptional activator Jun-C͞D, are known to either be up-regulated or more active in some cancer cells (22)(23)(24)(25)(26)(27)(28)(29). Thus, the phosphopeptides displayed on cancer cells and not JY BLCL are preferentially derived from source proteins associated with cytoplasmic signaling pathways and cellular transformation.…”
Section: Resultsmentioning
confidence: 99%
“…for c-ras Ha activation observed in earlier KA studies (Corominas et al, 1989), exhibiting moderate elevation in MAP kinase signalling (Parsons, 2004;Downward, 2004;Karin, 1995) and overexpression of cyclin D1 (Bamberger et al, 2001;Burnworth et al, 2006) or cyclin E2 (Di Cristofano et al, 2001;Weng et al, 2001). Incremental increases in keratinocyte proliferation culminated in very high BrdU labelling indices in papillomatous KA histotypes, with typical delays in expression of differentiation markers and the appearance of focal keratin K13 expression, an early marker of tumour progression (Greenhalgh et al, 1995).…”
Section: Hk1fos/δ5ptenmentioning
confidence: 87%
“…HK1.fos papillomas (Fig. 5, PAP lane) exhibited increased cyclin D1 and cyclin E2 expression (Bamberger et al, 2001), together with very high levels of activated P-ERKs 1/2 expression (Fig. 4, lanes P, HP and N), which suggested that MAP kinase signalling during wound-promoted HK1.fos papillomatogenesis facilitated escape from AKT-linked countermeasures (above) and restored P-AKT activity (Segrelles et al, 2006).…”
Section: Hk1fos/δ5ptenmentioning
confidence: 90%
See 1 more Smart Citation
“…In osteosarcoma and endometrial carcinoma, c-Fos overexpression was associated with high-grade lesions and adverse outcome (Gamberi et al, 1998;Bamberger et al, 2001). In a comparative analysis between precancerous lesion of the cervix uteri and invasive cervical cancer, c-Fos expression was significantly lower in precancerous lesions (Prusty and Das, 2005).…”
mentioning
confidence: 99%